Phytochemical Screening of Coleus aromaticus and Leucas aspera and Their Antibacterial Activity against Enteric Pathogens - Shiney ramya, B (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In the present study, two important medicinal plants Coleus aromaticus and Leucas aspera were assessed for phytochemical components and antimicrobial activity. The organic solvents viz., methanol and ethanol were used for the extraction of plant material. The extracts were screened for the presence of phytochemical compounds and also tested antibacterial activity against enteric pathogens such as Shigella sp., Salmonella typhi and Escherichia coli. The results revealed that the two plant extracts contained tannins, alkaloids and glycosides. The alcoholic leaf extracts (methanol & ethanol) of both of the plants leaf exhibited antibacterial activity against enteric pathogens such as Shigella sp., Salmonella typhi and Escherichia coli. The aqueous crude extracts of plants leaf did not show any antibacterial activity against the tested enteric pathogens. Hence, concluded that plant leaf extracts showed antibacterial properties due to the presence some phytochemical compounds.